2015
DOI: 10.1080/02626667.2014.993987
|View full text |Cite
|
Sign up to set email alerts
|

A method to disaggregate monthly flows to daily using daily rainfall observations: model design and testing

Abstract: A monthly to daily streamflow disaggregation method is presented as part of an emerging water quality model designed to link with established monthly hydrology and yield models. The daily time step is assumed necessary for simulating water quality dynamics. The method is tested on two catchments in South Africa where observed daily flow data are available. The model includes a volume correction process to ensure daily sums are equal to input monthly flows and this reduces the sensitivity of the results to some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The approaches used and the validity of the WQSAM model have been validated in previous studies, including the monthly-to-daily flow disaggregation (Slaughter et al, 2015;Hughes and Slaughter, 2016) and the water quality modelling processes Slaughter, 2017), which include simulations of salinity as total dissolved solids (TDS), nutrients (nitrates plus nitrites, phosphates and ammonia) and microbial water quality, illustrating that the approach adopted by WQSAM is appropriate for modelling water quality in South Africa under conditions of limited observed data and management capacity.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…The approaches used and the validity of the WQSAM model have been validated in previous studies, including the monthly-to-daily flow disaggregation (Slaughter et al, 2015;Hughes and Slaughter, 2016) and the water quality modelling processes Slaughter, 2017), which include simulations of salinity as total dissolved solids (TDS), nutrients (nitrates plus nitrites, phosphates and ammonia) and microbial water quality, illustrating that the approach adopted by WQSAM is appropriate for modelling water quality in South Africa under conditions of limited observed data and management capacity.…”
Section: Introductionmentioning
confidence: 90%
“…Gorgens and de Clercq, 2006;Piesold et al, 2007), the adoption of a routinely-used water quality model within management agencies in South Africa has been hampered by the lack of observed data with which to calibrate these models and insufficient technical expertise to accurately set up these models. This led to the development of the Water Quality Systems Assessment Model (Slaughter et al, , 2015Hughes and Slaughter, 2016;Slaughter, 2017;Slaughter and Mantel, 2017a), which specifically links to the routinely-used systems models in South Africa, namely the WRYM and WReMP models, and subscribes to an approach of requisite simplicity (Stirzaker et al, 2010) by only representing processes that explain the majority of variation of observed water quality data.…”
Section: Introductionmentioning
confidence: 99%
“…Sub daily rainfall is seldom available to modellers; pragmatically SASYM needs to run on a daily time step if processes are to be effectively simulated. Inputs to the Pitman model are daily rainfall but as the conventional model runs on a monthly time step the generated flows must be disaggregated to daily using a monthly-daily flow disaggregation method [39].…”
Section: Runoff Modelling and Catchment Zonesmentioning
confidence: 99%
“…Daily flows (m 3 s −1 ) are required for the erosion estimation. These can either be an unbroken time series of observed daily flow, daily flow estimated from a daily hydrological model such as the Agricultural Catchments Research Unit (ACRU) model [17], or monthly flow simulated from a monthly hydrological model such as the Pitman Model [38] disaggregated to daily using a monthly to daily disaggregation routine (e.g., [39]).…”
Section: Fundingmentioning
confidence: 99%
“…The application of existing internationally developed water quality models to South African catchments is hindered by the aforementioned constraints on observed data and modelling expertise. Within this context, the Water Quality Systems Assessment Model (WQSAM) (Hughes and Slaughter, 2016;Slaughter et al, 2015) was designed to use the available observed water quality data and to simulate water quality data that are useful for water resource management in South Africa, in that WQSAM takes as input, flow data generated by routinely used systems models, and water quality data are simulated in a form that is able to provide an estimate of risks associated with management decisions. WQSAM has initially focused on simulating nutrients, as eutrophication is arguably currently the most pressing water quality issue within freshwater resources in South Africa.…”
Section: Introductionmentioning
confidence: 99%